ANALYSIS OF ALUMINUM SAND CASTING OF A THREE-BLADED PROPELLER FOR FISHING BOATS WITH A DIRECT GATING SYSTEM - Umar, Mega Lazuardi; Hanafi, Agung Fauzi (Aurelia Journal, 2025)
This research aims to simulate and verify the aluminum material casting process using the sand casting method with a top gating system for traditional fishing boats. Numerical simulations were conducted to predict molten metal flow, solidification, and potential casting defects, specifically shrinkage porosity. Using the simulation method, the shrinkage porosity area was observed at the central point of the propeller shaft and alsoat the tips of the propeller blades. Consistent results were also verified by experiments. To improve the casting results, direct gating casting recommendations are presented but still show shrinkage porosity in the riser, shaft, and propeller blade tips. However, when compared to the results before the improvement, a reduction in shrinkage defects is evident. This research is expected to provide a better understanding of the optimization of gating system design in propeller casting using the sand casting method, thereby improving product quality and reducing the potential for defects in propellers used for traditional fishing boats.